Pengembangan instrumen evaluasi mata pelajaran biologi SMA kelas X di SMA Panjura Kota Malang - Tania Puspa Chandra; Triastono Imam Prasetyo; Agung (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
2013 curriculum is a competency-based curriculum. An evaluation instrument is used to measure the students" competence in the learning. The evaluation instruments developed in this research were 34 multiple choice guestions with a single answer from 5 answer choices, guestions with description answer, and 3 performance assessments. The multiple choice guestion with a single answer refers to the guestion's indicator that developed from the competency's indicator. Basic competency is a reference for the formulation of competeney's indicators. Performance assessment refers to basic competencies. The objectives of the research are: 1) develop the multiple choice guestions with a single answer of basic competencies 3.4, 3.5, and 3.6, 2) develop the performance assessment of basic competencies 4.4. 4.5, and 4.6. The research used ADDIE research model which consists of 5 stages (1) analysis, (2) planning, 3) development, (4) implementation, (5) evaluation. Data collection is obtained from logical validation by evaluation experts, material experts, and field experts, and empirical validation which includes difTiculty level, diflerentiation, reliability and distractor analysis. The result of the research is the multiple choice guestions with a single answer is known that the validity of the guestions'construct is compatible with the guestion's indicator. As for the validity of the content, known that the test material is compatible with the guestion's indicator, Empirical validation Of results on the small group trials results on multiple choice guestions with a single answer to the dificulty level obtained the ratio of easy problem-moderate-difficult to achieve 4:4:2, the diflerenee is obtained the largest percentage of 52,95”4 good category. For the analysis of distractor, he choice of answers outwit percentage is 41.1796. In addition, revisions were made for small group trials, Results of large group test product of difficulty level obtained the ratio of easy problem:medium:difficult to reach 4:4:2. Different power obtained the largest percentage of 41.17 percent good category. Reliability is very high that is 0.855, For the analysis of distractor, the choice of answers outwit percentage is 82.36 percent. Revisions are also made based on empirical empirical analysis results of large groups.   Kurikulum 2013 merupakan kurikulum berbasis kompetensi. Untuk mengukur kompetensi siswa dalam pembelajaran digunakan instrumen evaluasi. Instrumen evaluasi yang dikembangkan dalam penelitian ini adalah 34 soal pilihan ganda jawaban tunggal dengan $ pilihan jawaban, soal uraian dan 3 asesmen kinerja. Soal pilihan ganda jawaban tunggal mengacu pada indikator soal yang dikembangkan dari indikator kompetensi. Kompetensi dasar merupakan acuan perumusan indicator kompetensi. Asesmen kinerja mengacu pada kompetensi dasar. Tujuan penelitian yaitu: 1) merumuskan soal pilihan ganda jawaban tunggal dari kompetensi dasar 34, 35, dan 3.6, (2) merumuskan asesmen kinerja dari kompetensi dasar 4.4, 4.5 dan 4,6. Model penelitian menggunakan ADDIE yang terdiri dari 5 tahap yaitu: (1) analisis, (2) perencanaan, (3) pengembangan, (4) implementasi, (5) evaluasi. Pengumpulan data diperoleh dari hasil validitas logis oleh ahli evaluasi, ahli materi, dan ahli lapangan, dan validitas empiris meliputi tingkat kesukaran, daya beda, reliabilitas dan analisis pengecoh. Hasil penelitian yaitu soal pilihan ganda jawaban tunggal diketahui validitas konstruk soal sudah sesuai dengan indikator soal, validitas isi diketahui materi tes sesuai dengan indikator soal. Hasil validitas empiris pada uji coba kelompok kecil soal pilihan ganda jawaban tunggal untuk tingkat kesukaran diperoleh rasio soal mudah-sedang:sukar mencapai 4:4:2, daya beda diperoleh persentase terbesar yaitu 52,956 kategori baik. Analisis pengecoh berfungsi sebanyak 41,1796. Berdasarkan uji coba kelompok kecil dilakukan revisi. Setelah dilakukan validitas logis dan empiris dilakukan revisi untuk digunakan uji coba kelompok besar. Hasil uji coba kelompok besar tingkat kesukaran soal diperoleh rasio soal mudahssedangssukar mencapai 4:4:2. Daya beda diperoleh persentase terbesar 41,1796 kategori baik. Reliabilitas tergolong sangat tinggi yaitu 0,855, Analisis pengecoh berfungsi sebanyak 82,366. Revisi dilakukan berdasarkan hasil analisis validasi empiris kelompok besar.